Effects Of Temporary restriction Law & Practice (Latakia University Journal - Economic and Legal Sciences Series, 2020)
A temporary restriction is considered a violation of the principle of the absolute proven power of the real estate registrations, so the final confirmation of the right to the owner of the restriction prevents the possibility of observing the subsequent restrictions on temporary restriction. which is if it does not prevent the person who registered the property for his name from disposing of it, but it leads to freezing the property in reality and preventing the disposing of it, So that others are reluctant to deal with its owner and they  take care before taking any action, so  the Syrian legislator has taken precautions for this and specified short deadlines that, after its expiry, it is imperative that the temporary restriction be deleted by the force of law.This study aimed at explaining the legal implications of the registration  the temporary registration, and how courts address it in the light of jurisprudence and the jurisprudences of the judiciary.